Rehospitalization in Schizophrenia: Socio Demographic and Clinical Correlates - N Parikh, Minakshi; C Parikh, Nimesh; R Patel, Poorav (International Journal of Medical Research and Review, 2014)
Introduction: Rehospitalisation is an important research tool with two major utility aspects. It is a reliable and valid measure for assessing the course of schizophrenia and a measure of hospital effectiveness. Objectives: The study aimed at finding out the rate of rehospitalization and comparing the various socio-demographic and clinical correlates of rehospitalization in schizophrenia and the reason for rehospitalization amongst first admissions and rehospitalizations. Material and Method: It was a cross sectional study using DSM – 4 and a specially designed semi structured proforma carried out in 50 consecutive indoor patients of schizophrenia who were grouped into two: first admissions and rehospitalization. These two groups were compared regarding socio-demographic and clinical variables using the SPSS version 20for probability. Results: A substantial 54% of the total patients were rehospitalisation cases. 85.19% of the readmitted group had illness duration of more than 2 years. Non-medical treatment sought by patient’s relatives before hospitalization was 73.91% among the first admission as compared to only 18.51% (P<0.05) of rehospitalization group. Rehospitalizations were positively and significantly correlated with older age, low educational level (p<0.05) and low income level. Conclusion: We observed that de novo cases wasted significantly more time before coming for treatment which stresses the need for psychoeducation of schizophrenia caretakers. Our study also found that economic status and education level significantly affect rehospitalisation. This highlights importance of socioeconomic factors in the prediction of rehospitalisation along with clinical correlates.